Experimental and computational evaluation of thermal performance and overheating in double skin facades - Hernandez Tascon, Mauricio (2008)
Double Skin Facades (DSFs) have been developed as an alternative technology to improve the thermal performance of conventional fully glazed buildings. Nevertheless, there is little test information on the behaviour and real performance of DSFs. This is specifically the case when the facade has to perform under extreme or moderate summer conditions. The characteristics of thermal overheating of a specific type of DSF with various configurations and its practical control have not been subjected to systematic experimental and computational investigations. This research which is based on an existent load of knowledge, carried out experiments of a full-scale one-storey laboratory chamber of a selected type of Double Skin Facade in which a comparative analysis of the thermal performance is assessed, CFD simulations of the experimental model and a Field Case Study of an existing building in the United Kingdom is also monitored. The basic thermal behaviour in the facade cavity and adjacent room is investigated by a series of parametric studies and basic flow field investigations. Section models of the DSF chamber and the case building were made and modelled using CFD in order to visualise the thermal and airflow behaviour inside the DSF complementing the experimental and field work.